Archaeology and History of Peasantries 2. Themes, Approaches and Debates. - Kilby, Susan (Medieval Settlement Research, 2023)
This volume is the second in a series examining preindustrial peasant communities across Europe, with a particular focus on the Iberian Peninsula. The series springs from the project ‘Peasant agency and sociopolitical complexity’, which ran between 2018–21, and was funded by Spain’s Ministry of Science and Innovation. While ostensibly interdisciplinary in nature, Volume One focused on archaeology, whereas this volume meets that objective more readily, with contributors drawing on history and sociology in addition to archaeology in a variety of forms. A supplementary focus for this volume is ‘to explore … new theoretical and methodological approaches’ to the study of pre-industrial peasant society across Europe.